IL-13 directly promotes esophagus production of CCL11 and CCL24 and the migration of eosinophils - Neilsen, C. V. (2009)
BACKGROUND: Eosinophilic esophagitis (EE) is a clinico-pathological defined esophageal disorder that is characterized by eosinophil migration into esophageal tissues. There is growing support for EE being an allergic disease and for a contribution of Th2-associated cytokines in disease pathogenesis. The respiratory system has been shown to be critical in driving the development of EE in animal models. However, the mechanisms underlying the recruitment of eosinophils into the esophagus remain unclear. OBJECTIVE: We sought to investigate the influence of Th2-associated cytokines on the production of eosinophil-specific chemokines from the esophagus directly. METHODS: In order to eliminate the potential involvement of the lung, we utilized isolated esophageal rings. These were treated in vitro with IL-4 or IL-13 and the expression and production of CCL11 and CCL24 determined. RESULTS: Our data demonstrates that IL-13 is a potent and direct inducer of both CCL11 and CCL24 production from the esophagus, as is IL-4 also. The expression of CCL11 precedes CCL24 by several hours but is then diminished over time, as well as at high concentrations of IL-13. We demonstrate that there is an up-regulation of the inhibitory IL-13 receptor, IL-13Rα2 but that IL-13Rα1 remains unaltered. Esophagus rings isolated from STAT6(-/-) mice were unable to produce CCL11 or CCL24 upon IL-13 treatment. Lastly, we demonstrate that esophageal production of CCL11 and CCL24 upon IL-13 stimulation is sufficient to promote eosinophil migration. CONCLUSIONS: IL-13 is capable of directly stimulating esophageal tissue to produce eosinophil-attracting chemokines and drive eosinophil migration.